2014
DOI: 10.15230/scsk.2014.40.3.297
|View full text |Cite
|
Sign up to set email alerts
|

Cell migration and Anti-inflammatory Effect of Red Ginseng Extracts Fermented with Laetiporus Sulphureus

Abstract: Red ginseng (RG) contains specific ginsenosides (Rg2, Rg3) which show various pharmacological effects and absorption rate in the body better than panax ginseng. Therefore many people have been used it for health for a long time. Furthermore, many researchers have been studying its biological activities for a long times because fermentation generates lots of beneficial small molecules good for health. In this study, we fermented red ginseng with mycelium of Leatiporus sulphures var. miniatus for 7 days. As a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2017
2017
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
1
0
1
Order By: Relevance
“…Previous studies have reported various compounds derived from L. miniatus, which include polysaccharides, benzofuran glycoside, acetylenic acid, lanostanoid triterpene and β-1,3-1,4-glucanase [16][17][18][19]. Other investigations have shown that extracts and specific fractions obtained from L. miniatus have various positive biological and pharmacological activities, including anti-tumor [20][21][22], anti-inflammatory [23,24], anti-microbial, and anti-fungal activities. Some of these properties observed were seen with the hexane fraction isolated from L. miniatus lipid extracts [25]; while, specifically, anti-oxidant activities were seen with its hot water soluble and hot alkali soluble polysaccharides [26].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported various compounds derived from L. miniatus, which include polysaccharides, benzofuran glycoside, acetylenic acid, lanostanoid triterpene and β-1,3-1,4-glucanase [16][17][18][19]. Other investigations have shown that extracts and specific fractions obtained from L. miniatus have various positive biological and pharmacological activities, including anti-tumor [20][21][22], anti-inflammatory [23,24], anti-microbial, and anti-fungal activities. Some of these properties observed were seen with the hexane fraction isolated from L. miniatus lipid extracts [25]; while, specifically, anti-oxidant activities were seen with its hot water soluble and hot alkali soluble polysaccharides [26].…”
Section: Introductionmentioning
confidence: 99%
“…또한 대식세포에 그람 음성세균의 세포외막 에 존재하는 내독소 lipopolysaccharide(LPS)에 의해 tumor necrosis factor-α(TNF-α), interleukin-1β(IL-1β) 및 interleukin-6(IL-6) 등과 같은 cytokine의 분비를 증가시킨다 (17). 또한 iNOS에 의해 생성되는 NO와 cyclooxygenase-2 (COX-2)에 의 해 생성되는 prostaglandin E2(PGE2)등의 염증유발인자들도 생성된다 (18,19). 이러한 염증유발인자들은 NO와 ROS의 생성을 더 자극하게 되어 염증 반응이 과도해지며 이러한 현상은 만성 염증 질환의 원인이 된다.…”
unclassified